Walking for Transportation on Campus: Perspectives from Faculty and Students - McMullen, Jennifer; Kercsmar, Sarah; Poole, Kimberly; Ickes, Melinda J. (Building Healthy Academic Communities Journal, 2020)
Background: Walking is a recommended strategy for meeting physical activity (PA) requirements and benefiting from associated health outcomes. Walking for transportation, which is walking to get from ”Point A” to ”Point B,” may help individuals in fulfilling their weekly recommended PA, though little research has been done as it relates to walking for transportation on a college campus. Aim: To qualitatively explore attitudes and barriers toward walking for transportation and cues to action among a convenience sample of faculty, staff, and students. Methods: Through a non-experimental design, qualitative data were collected through conducting focus groups (n = 10) at a public, southeastern university with college students, staff, faculty (n = 13 students; n = 25 staff; n = 19 faculty). Results: The main themes emerging included: definitions of walking for transportation, factors that encouraged walking for transportation, barriers to walking on campus, and campaign/incentive suggestions. Conclusion: Findings support previous research which indicates situational factors prohibit individuals from walking for transportation. Further, findings indicate it would be of value for future research to determine best practices for promoting and incentivizing walking across various sub-groups not explored in this study. Lastly, point-of-decision prompt use (i.e., campus signage to promote walking) should be explored as a strategy to promote walking and active transport to determine what various groups respond most positively to.